Geoheritage - Page, Kevin; SpringerLink (Online service) (Berlin/Heidelberg : Springer Berlin Heidelberg : Imprint: Springer.)
The Geoheritage journal is an international journal dedicated to discussing all aspects of our global geoheritage, both in situ and portable. The journal will invite all contributions on the conservation of sites and materials - use, protection and practical heritage management - as well as its interpretation through education, training and tourism. The journal wishes to cover all aspects of geoheritage and its protection. Key topics are: - Identification, characterisation, quantification and management of geoheritage; - Geodiversity and geosites; - On-site science, geological and geomorphological research: - Global scientific heritage - key scientific geosites, GSSPs, stratotype conservation and management; - Scientific research and education, and the promotion of the geosciences thereby; - Conventions, statute and legal instruments, national and international; - Integration of biodiversity and geodiversity in nature conservation and land-use policies; - Geological heritage and Environmental Impact Assessment studies; - Geological heritage, sustainable development, community action, practical initiatives and tourism; - Geoparks: creation, management and outputs; - Conservation in the natural world, Man-made and natural impacts, climate change; - Geotourism definitions, methodologies, and case studies; - International mechanisms for conservation and popularisation - World Heritage Sites, National Parks etc.; - Materials, data and people important in the history of science, museums, collections and all portable geoheritage; - Education and training of geoheritage specialists; - Pedagogical use of geological heritage - publications, teaching media, trails, centres, on-site museums; - Linking the United Nations Decade of Education for Sustainable Development (2005- 2014) with geoconservation.
Keywords: Historical geology; Geobiology; Regional planning; Urban planning; Physical geography; Historical Geology; Physical Geography; Biogeosciences; Paleontology; Landscape/Regional and Urban Planning; Mineralogy